Penguatan Primary Care di Era Jaminan Kesehatan Nasional - Silvia Nurvita; Aerrosa Murenda Mayadilanuari; Dody Indra Sumantiawan; Viny Natalia Dewi; Aldi Rizki Yudistira; Annisa Dias Oktanida; Maria Gisela Dora Kelen; Vina Budi Lestari; Sulis Setyowati; Yoel Pramuditya; Diah Rahma Pertiwi; Lie Eraldo Manason; Penta Putri Nunik Yuniarti (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background: The JKN program is here to provide benefits to Indonesian citizens in the form of comprehensive individual health services. The number of JKN participant referrals from FKTP to FKRTL has increased. Therefore, it is necessary to conduct research on strengthening basic health services to minimize the increase in health service costs borne by BPJS. Method: This study is a descriptive type of research because it is to describe how to optimize primary care. Data collection uses literature studies. Results: Based on a review of the four studies above from various countries, strengthening primary care is important to do by means such as integrating client-centered health services at the health center level, increasing community involvement when sick for treatment, optimizing the role of the government, implementing the Family Health Team approach, and routinely conducting socialization of JKN benefits in primary care. Conclusion: JKN provides benefits to improve public health so that strengthening primary health services is needed to help reduce inefficiencies in health service costs while increasing access to comprehensive and patient-centered health services.